Analytical comparative study of the Umayyad mosaics in Tiberius and Jericho - Hassan, Gamal Abdel-Rehem Ibrahim; Hamadneh, Khayriah Mohammad Hamdan (Journal of Humanities & Social Sciences, 2021)
The aim of the research was to analyze the artistic decorations of the mosaic of the ancient Umayyad civilization in Palestine in the light of a comparative study between the most important umayyad palaces in Khirbet al-Minya in Tiberias and Khirbet al-Masrif in Jericho.There is no doubt that the archaeological site of Khirbet al-Monaina in Palestine has played a major role in the decoration of floors and walls, where we find it covering the dome above the top of the huge hall of the palace and take geometric and floral motifs, in addition to covering some of the floors of rooms filled with many mosaics of various shapes and use.On the other hand, there is a consensus among archaeologists and Islamic arts that the ruins of Khirbet al-Mafjar are unique architectural buildings in Palestine, which represent one of the important examples in the history of Islamic art in the Umayyad period, because of its possession of fine art decorations and various materials of plaster, in addition to mosaic floors and frescoes, as well as buildings rich in examples of patterns used by the Umayyads in architectural decoration.After the comparative analytical study of the Umayyad mosaic in Khirbet al-Mania in Tiberias and Khirbet al-Mafjar in Jericho, the research found out and discovered the similarities and differences between them.
Keywords: Umayyad mosaic; mosaic technique; mosaic comparison